A comparative study of correlations of critical heat flux of pool boiling. Issue 1 (2nd January 2017) - Fang, Xiande; Dong, Anqi
ABSTRACT: Nucleate pool boiling is desirable for many engineering systems. One challenge task for designing a system with nucleate pool boiling is to estimate the critical heat flux (CHF), which needs an accurate pool boiling CHF correlation. A few evaluations of pool boiling CHF correlations were reported, which used limited experimental data or covered limited correlations, resulting in inconsistent results. Therefore, it is difficult to determine which one is more appropriate for a given application. In this paper, a database containing 600 data points of pool boiling CHF of 12 pure liquids on plain surfaces having orientation angles of 0°−180° is compiled from 40 published papers. The reduced pressure is from 0.0001 to 0.98, and the 13 fluids are water, helium, nitrogen, hydrogen, R113, FC-72, FC-87, HFE-7100, ethanol, benzene, hexane, pentane, and methanol. With the database, 21 pool boiling CHF correlations are assessed. The most accurate one has a mean absolute deviation of 27.1%, indicating a need for developing more accurate correlations for engineering applications. Besides, the factors affecting the accuracy of correlations are analyzed and some valuable conclusions are obtained. The work lays a valuable foundation for the further study of pool boiling CHF correlations and provides a guide for choosing proper correlations for given applications. Several topics worthy of attention for future studies are suggested.